Influence of weather factors on separate periods of fungus Claviceps purpurea (Fr.) Tul development and level of ergot harmfulness in Kirov region - L. M. Shchekleina (Аграрная наука Евро-Северо-Востока, 2019)
In 2001-2017 in the conditions of Kirov region 36 winter rye varieties were assessed according to the character of interrelation in a "Secale cereale - Claviceps purpurea" pathosystem. The article provides the results of this research. For assessment of the change in meteorological conditions and their influence on ergot development the average daily air temperature and amount of precipitations from May 1 to May 31 (the period of screrotia germination) and from June 5 to June 15 (the period of plants infection) were used. The study of varieties was carried out by artificial inoculation of flowers with pathogen suspension. The ergot recording was carried out at a phase of milk-wax ripeness of grain according to infection of biocenoses (quantitative trait) and on contamination of grain mass with sclerotia (qualitative trait). At an artificial inoculation all rye varieties under study were infected by ergot in limits from 8.3 up to 100% that demonstrated their strong susceptibility to disease. Only 6 varieties (Falenskaya 4, Kirovskaya 89, Rada, Flora, Dymka, and Volkhova) were infected at the level of 8.3-27.3%, contamination of grain mass by sclerotia – 0.4-1.9%. The standard variety Falenskaya 4 had a high productivity and efficiency of plants (660 g/m2 and 11.0 g), which was characterized by a high degree of re-growth after infestation with a snow mold (100%), the smallest distribution of an ergot in sowing and contamination of grain mass with sclerotia. During the correlation analysis a close relation between the infestation of plants with an ergot and contamination of grain mass with sclerotia (r = 0.76) was established. The same immunological traits significantly influenced on the productivity (r = -0.67 and -0.55) and insignificantly - on plants efficiency. The positive dependence between immunological traits and 1000-grain mass was revealed. Possibly, sterilization of an ear leads to formation of a larger grain in fertile flowers (r = 0.42 and 0.37). The regression equations between the amount of sclerotia in an ear, mass of grain per ear and a number of grains in it have proved with 95-97% probability that with 1 sclerotium increase in contamination per ear, the grain mass per ear decreases by 0.18 grams, and the amount of grains per ear – by 4.7 pieces.